Beyond the pandemic: how COVID-19 will shape the serious and organised crime landscape in the EU (Europol, 2020)
Europol has been monitoring the impact of the COVID-19 pandemic on serious and organised crime and terrorism in the EU from the outset of the pandemic in Europe. Understanding ongoing developments and their impact on the internal security of the EU in times of crisis and communicating these insights to our partner law enforcement authorities is of vital importance in formulating effective responses at EU and national level. Europol’s monitoring efforts primarily rely on contributions received from law enforcement authorities in the Member States and our law enforcement partners across the world. Where necessary and appropriate, this information may be complemented with verified information from open sources.